Faktor-Faktor yang Berhubungan dengan Keluarga Sadar Gizi - Holil M.Par'i; Ichwannudin Ichwannudin; Fred Agung Suprihartono; Aryani Sudja (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2011)
Kadarzi is a family who knows the problems of nutrition and is able to prevent and overcome the problems ofmalnutrition in each family member. The family is called "Kadarzi" if it has applied good nutrition behaviourcontinuously. The development" of Kadarzi is influenced by many factors. The purpose of this research is toinvestigate the relationship of various factors including the quality of posyandu, maternal education level, familyincome level, family attendance routines and the distance to posyandu with Kadarzi. Indicators that are used inthe "Kadarzi" are exclusive breastfeeding, food diversity, use of iodized salt and the use of nutritionalsupplements. The study design was Cross Sectional, samples are families who have children under five with atotal sample of 410 families.The results showed that from the sample size of 79 posyandu, there are 38 posyandu (48,1%) have poorquality. Most mothers have completed primary school education level (59,0%). The Average family income is600.000 rupiahs. There are still 10,2% under five years old who are not routinely weighed at posyandu. TheAverage distance of the family to posyandu is 100 meters, but there are as many as 40,5% greater than thedistance. Judging from the quality of Kadarzi, as many as 39,8% are classified as poor. From the statistical testresult it is proven that family attendance routines to the posyandu has a significant relationship with Kadarzi(p<0,05). The logistic Regression test results showed that the family attendance routine to the posyandu is themost dominant factor formation of Kadarzi. To raise the awareness of families about nutrition, posyandu can be ameans to perform counseling and consultation of nutrition in the family. To increase the knowledge and skills ofcadres, the training cadre of Kadarzi requires great attention.